2021
DOI: 10.1096/fj.202002537rr
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic di‐GMP sensing histidine kinase PdtaS controls mycobacterial adaptation to carbon sources

Abstract: Cell signaling relies on second messengers to transduce signals from the sensory apparatus to downstream signaling pathway components. In bacteria, one of the most important and ubiquitous second messenger is the small molecule cyclic diguanosine monophosphate (c‐di‐GMP). While the biosynthesis, degradation, and regulatory pathways controlled by c‐di‐GMP are well characterized, the mechanisms through which c‐di‐GMP controls these processes are not entirely understood. Herein we present the report of a c‐di‐GMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Genetic deletion of pdtaS / R relieves this inhibition and restores wild-type stress resistance. Although the PdtaS GAF domain was recently reported to bind cyclic di-GMP ( Hariharan et al, 2021 ), the full set of ligands that interact with the PdtaS sensing domains are not known. To determine whether PdtaS/R directly senses cytosolic metals and/or nitric oxide, we reconstituted the PdtaS/R phosphotransfer reaction using purified proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic deletion of pdtaS / R relieves this inhibition and restores wild-type stress resistance. Although the PdtaS GAF domain was recently reported to bind cyclic di-GMP ( Hariharan et al, 2021 ), the full set of ligands that interact with the PdtaS sensing domains are not known. To determine whether PdtaS/R directly senses cytosolic metals and/or nitric oxide, we reconstituted the PdtaS/R phosphotransfer reaction using purified proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The kinase activity of purified PdtaS was also shown by Buglino et al (2021) to be regulated by zinc and copper, indicating that the PdtaRS pathway may have additional functions in regulating M. tuberculosis responses to these metals. Recently, the activity of the PdtaRS pathway has been shown to be regulated by intracellular levels of cyclic di‐GMP, which increases when Mycobacterium smegmatis is cultured in a nutrient‐poor medium to activate the PdtaRS TCS (Hariharan et al, 2021), implicating this system in the adaptation of M. tuberculosis to nutrient starvation during infection in addition to the aforementioned environments. Taken together, these in vitro models have begun to shed light on the role of TCSs in host adaptation during M. tuberculosis infection.…”
Section: Linking Two‐component Systems To Host Environmentsmentioning
confidence: 99%
“…Copper, Zinc, NO (Buglino et al, 2021), Cyclic di-GMP (Hariharan et al, 2021) Yes (Preu et al, 2012) PdtaR (Morth et al, 2005) No (Agrawal et al, 2015) NCA NCA MtrB NCA NCA MtrA (Friedland et al, 2007) PhoP, NarL, KdpE, TcrX, TcrA (Agrawal et al, 2015; Phosphotransfer not observed by Agrawal et al (2015).…”
Section: Pdtasmentioning
confidence: 99%
See 2 more Smart Citations